FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN DAN PENURUN PDRB SUMATERA UTARA - Tyana; Andrew; Winson; Frentyo; Devin (Bajang Institute, 2022)
Economic development can be carried out if an area experiences an increase in economic growth. Therefore, a study was conducted to find the factors that influence the decline and increase in PDRB in North Sumatra algo gives recommendations to increase the regional income. PDRB data from 2015 to 2020 is presented above constant prices to find out the rate of PDRB growth over time. The results of the data analyzed show that the factors that influence the increase and decrease in GDP are investment, consumption, government spending, and export and import. In 2022, the North Sumatra Government can focus on lowering and lowering the first level first. Then it can carry out equitable development by improving service infrastructure, improving digital infrastructure, improving the economy in the tourism and MSME sectors and optimizing productivity in order to achieve increased income.